Philosophical Meaning for Justice Based on the One Godhead in Judge's Decision - Wahyudi Kurniawan; Sholahuddin Al-Fatih (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
This study aims to analyze the meaning of philosophy in the court decision "For Justice Based on God Almighty" in a Judge's Decision based on the Law of the Republic of Indonesia Number 48 of 2009 concerning Judicial Power in the era of the Covid-19 pandemic. This research is normative juridical research with primary legal materials, secondary legal materials, and tertiary legal materials. The methods and tools for collecting legal materials use the method of documentation and document study. Data analysis was carried out qualitatively on the legal materials owned. The results of the research and discussion explain that the meaning of "For the sake of Justice the Almighty" is very closely related to respond to God Almighty, the creator of life, not only related to justice seekers. Not only within the scope of the judge's responsibility to justice seekers and the general public but spiritually it is the spiritual judge's responsibility to God Almighty.